The role of bank monitoring in borrowers׳ discretionary disclosure: Evidence from covenant violations - Vashishtha, Rahul (Journal of Accounting and Economics, 2014)
This study uses covenant violations to provide evidence on how firms make disclosure decisions in the presence of enhanced bank monitoring. Using a regression discontinuity design, I find that firms reduce disclosure following covenant violations. A series of analyses suggest that part of this decline in disclosure reflects a delegation of monitoring to banks by shareholders who consequently demand less disclosure.